Tuning the magnetoelastic transition in (Mn, Fe)2(P, Si) by B, C, and N doping. (November 2016) - Miao, X.F.; Thang, N.V.; Caron, L.; Yibole, H.; Smith, R.I.; van Dijk, N.H.; Brück, E.
Abstract: The critical temperature and first-order character of the magnetoelastic transition in (Mn, Fe)2 (P, Si) are tunable by doping the structure with B, C and N atoms. Neutron diffraction experiments reveal that B substitutes Si on the 1 b site of the hexagonal P-62m structure, C occupies the interstitial 6 j and 6 k sites, while N distributes on both the 1 b and interstitial 6 j and 6 k sites. The tuning mechanism has been discussed in terms of the subtle variations in electronic configuration around the Fe atoms, which can be used to tailor the magnetoelastic transition. Graphical abstract: